PEMBERDAYAAN EKONOMI MASYARAKAT DALAM MENCIPTAKAN DESA MANDIRI DAN CEK KESEHATAN GRATIS - Wiwik Saidatur Rolianah; Kholid Albar; Lidia Adimata Putri; Luluk Yuliati; Hafidhotul Mufidah; Yusda Auliyah (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The purpose of the community service program is to help increase community awareness in creating independent villages with the role of women. This is done because data in Sidokumpul Village states that some women work as farmers or housewives whose daily life still relies on income from their spouses or husbands. Therefore, it is hoped that the role of women or mothers in Sidokumpul Village, Bungah District, Gresik Regency, East Java Province can process agricultural products and earn income to help meet their daily needs. If the husband's income is added to the income from mothers or women, the level of family welfare will certainly increase and can help the village economy and create an independent village with more innovative women's work in managing agricultural products, then the better income is usually accompanied by attention to public health. The method used for community services activities is discourse and discussion in front of the participant’s mothers, a total of 40 enthusiastic participants participated in the event.